Crossroads of the classroom - Ross, Vicki, 1958-; Chan, Elaine; Keyes, Dixie (Bingley : Emerald Publishing Limited, 2017)
This book aims to explore and make visible the intersection of subject matter knowledge and teacher knowledge in the narratives of teachers. This complicated interaction between these two bodies of knowledge is often studied and little understood.This book uses narrative to examine the complexities of teaching and learning. The authors of the chapters, as well as the editors, use innovative approaches to narrative methodology for research on teaching and teacher education in areas of education critical to teachers' lives. Particularly through this book, they continue to advance the work of researchers to display narratives of educator lives and ways of knowing while opening the space for a community of narrative scholars.
Prelims -- Teachers' stories of navigating the intersection of subject matter and teacher knowledge -- Section I: Entering the crossroads through stories at the elementary level -- Variegated stories of professional development: striking A/N IM/Balance between science and mathematics content knowledge and teacher knowledge -- Stories and statistics: a mixed picture of gender equity in mathematics -- A glimpse into the future: practice teaching in fifth-grade math -- Choosing the best alternative: the branching pathways of consequences in social studies curriculum choice-making -- Section II: Entering the crossroads through stories from the secondary level -- Sing it over: meditations on best-loved self and sustaining in secondary english language arts -- Teaching that promotes diversity: the potential of disruptive narratives -- Stories of an english language arts teacher in a high need secondary school: a narrative inquiry into her best-loved self -- Health, physical education content, and teacher knowledge/identity -- Section III: Entering the crossroads through stories from teacher preparation -- A narrative inquiry of other in special education: tensions of subject matter knowledge in relation to teacher knowledge -- Interweaving narratives of personal and professional selves of a beginning teacher in India -- Traditional teaching method still holds water: narrative inquiry of student teachers' professional identities at the Intersection of teacher knowledge and subject matter knowledge -- Indigenous education, relational pedagogy, and autobiographical narrative inquiry: a reflective journey of teaching teachers -- Narrative resonance among stories: crossroads of the classroom, curriculum-makers, and complexities of deliberation -- About the Authors -- Index.
Includes bibliographical references and index.
Keywords: Education, Distance, Open & Online Education; Educational equipment & technology, computer-aided learning (CAL).; Education -- Research -- Methodology; Narrative inquiry (Research method); Effective teaching